Prevalence of Campylobacter spp. in broilers in North Lebanon - Rana Awada; Ghassan Ghssein; Ali El Roz; Mona Farhat; Nada Nehme; Hussein F. Hassan (Veterinary World, 2023)
Background and Aim: Great attention has been given recently to the prevalence of different Campylobacter spp. in poultry since the latter are considered the major contributing reservoir of human campylobacteriosis. In Lebanon, the occurrence of campylobacteriosis in humans is high. The aim of our first-of-its-kind study in the country was to estimate the prevalence of Campylobacter spp. in broilers from a convenient sample of farms in North Lebanon.